Intelligent Multi-Keyword Ranked Searchable Security Algorithm - et. al., K. Madan Mohan, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
enterprises are moving their valuable information to the cloud because of the advantage that storage as a service brings. Reliability is at the heart of the cloud service and relationship. We use the sense of security when establishing trust. Trust is established through cryptography. Searchable encryption is a method to provide security. Literature research workers have been studying searchable encryption schemes. We will focus on advanced techniques that leverage CRSA and B-Tree to enhance level of trust. We conducted a search on encrypted data using the Azure cloud platform.